PEMIKIRAN SUFISTIK NURCHOLISH MADJID - MOHAMAD AFIF (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2015)
Nurcholish Madjid (Cak Nur) is well known especially among Indonesian middle class and well-educated group in Indonesia. Between the 1970s and the 2000s, his thoughts, received great attention because his ideas about the renewal of Islamic thought were to some extent controversial. Nevertheless, there are still many people who do not know Cak Nur's thought outside the field of the renewal of Islamic thought . In fact, as a qualified and knowledgeable scholar, Cak Nur talked in many ways and in many fields of Islam , one of them is Sufism. Just like his thinking in the field of renewal which are weighty and meaningful, his thought in Mysticism was also pivotal. Therefore it is important to introduce his thinking widely to the public in order to take benefit from it.Key words: Nurchulis Madjid, Sufism, Neo -Sufism